NEWPROG: um ambiente online para crianças aprenderem programação de computadores - Torezani, Carpegieri (2014)
This dissertation presents the development of a web environment with digital resources for children to learn programming. When children develop programming activities, specially planned by the teacher and prepared with the resources created in this work, undergo a process of development of their cognitive skills such as: Troubleshooting, Autonomy, Planning, Self-Regulation and Critical Spirit. The following digital resources were developed: 1) EANewProg - an Editor of Programming Activities that allows teachers to edit activities to be presented to children and 2) NewProg - an environment for children to visualize activities, edit and evaluate solutions. The NewProg also stores a history of activities (learning path) developed by the child, so that the teacher can monitor and plan the most suitable learning activities to each child.